Critical Distinctions between Expert and Novice Translators: Task and Professional Satisfaction - Rodríguez-Castro, Mónica (HERMES - Journal of Language and Communication in Business, 2019)
The nature of translation projects and tasks in the language industry has undergone significant changes due to a widespread adoption of the subcontracting model and recent technological trends. Managing increasing terminological complexity, higher task specialisation, and higher levels of technical expertise have become essential elements of a translator’s professional profile. Nonetheless, the requirement of such a sophisticated professional profile has challenged novice translators in their incipient careers because of limited knowledge and training opportunities. Since many changes have occurred to the profession over a relatively short span of time, this article studies sources of translator satisfaction and dissatisfaction that may affect their perception of work as well as the language industry at large. This study reports results from an ongoing investigation into the ‘expertise effect’ measured through translator satisfaction in relation to two main categories: (a) professional satisfaction and (b) task satisfaction. A student’s t-test is used to compare perceptions of novice and expert translators (N=250), and the results suggest a gap in critical sources of satisfaction between the two populations. The findings could be applied to determine possible means of mitigating career turnover among translators and used by translator trainers to comprehend the needs of novice professionals.